Protocol for the collaboration between the national genebank and community seed banks - CGIAR Research Program on Climate Change, Agriculture and Food Security (2021)
The protocol was developed through a collaborative process and launched at the Guiding Seed Sector Transformation Conference of the ISSD Africa program. Kenya and Uganda endorsed the protocol, initiating new collaborative activities. The protocol was welcomed by many partners from around the world.